THE INFLUENCE OF LEADERSHIP, COMPENSATION, COMMUNICATION AND WORK ENVIRONMENT ON EMPLOYEE PERFORMANCE THROUGH ORGANIZATIONAL COMMITMENT AS AN INTERVENING VARIABLE (STUDY AT BANK KALTIMTARA SYARIAH SAMARINDA BRANCH - Rupi Rupi; Zainal Ilmi; Jiuarhardi Jiuarhardi (International Journal of Economics, Business and Accounting Research (IJEBAR), 2021)
Abstract: This study aims to analyze the influence of leadership, compensation, communication, and work environment on employee performance through organizational commitment as a banking intervention variable. IBM AMOS 23 was used to analyze the pattern of causality between variables. This research uses survey research methods. The population in this study were all staff at the Bank Kaltimtara Syariah Samarinda Branch in East Kalimantan. The number of research samples is determined by 250 respondents. The result of the research is that there is a significant direct and positive influence of leadership on employee performance. There is no significant negative direct effect of compensation on employee performance. There is a significant direct and positive effect of communication on employee performance. There is a significant direct and positive effect of the work environment on employee performance. There is a significant direct and positive effect of organizational commitment on employee performance. There is a significant indirect and positive effect of leadership on employee performance by intervening organizational commitment. There is a significant indirect and positive effect of compensation on employee performance by intervening organizational commitment. There is a significant indirect and positive effect of communication on employee performance with organizational commitment intervention. There is no indirect and insignificant negative effect of the work environment on employee performance by intervening organizational commitment. There is a significant direct and positive effect of organizational commitment on employee performance. There is a significant indirect and positive effect of leadership on employee performance by intervening organizational commitment. There is a significant indirect and positive effect of compensation on employee performance by intervening organizational commitment. There is a significant indirect and positive effect of communication on employee performance with organizational commitment intervention. There is no indirect and insignificant negative effect of the work environment on employee performance by intervening organizational commitment. There is a significant direct and positive effect of organizational commitment on employee performance. There is a significant indirect and positive effect of leadership on employee performance by intervening organizational commitment. There is a significant indirect and positive effect of compensation on employee performance by intervening organizational commitment. There is a significant indirect and positive effect of communication on employee performance with organizational commitment intervention. There is no indirect and insignificant negative effect of the work environment on employee performance by intervening organizational commitment. There is a significant indirect and positive effect of compensation on employee performance by intervening organizational commitment. There is a significant indirect and positive effect of communication on employee performance with organizational commitment intervention. There is no indirect and insignificant negative effect of the work environment on employee performance by intervening organizational commitment. There is a significant indirect and positive effect of compensation on employee performance by intervening organizational commitment. There is a significant indirect and positive effect of communication on employee performance with organizational commitment intervention. There is no indirect and insignificant negative effect of the work environment on employee performance by intervening organizational commitment. Keywords: Leadership, compensation, communication, work environment, organizational commitment and employee performance